MicroRNA-451a and Th1/Th2 ratio inform inflammation, septic organ injury, and mortality risk in sepsis patients - Geng, Feng; Liu, Wei; Yu, Li (Frontiers in Microbiology, 2022)
Aims: MicroRNA-451a (miR-451a) regulates Th1/Th2 cell differentiation, inflammation, and septic organ injury in several experiments. Therefore, the present study aimed to explore the inter-correlation of miR-451a with Th1/Th2 ratio, and their association with inflammation, septic organ injury, and mortality risk in sepsis patients. Methods: Consecutively, 117 sepsis patients and 50 healthy controls (HCs) were enrolled. Peripheral blood mononuclear cell samples were collected to detect miR-451a expression and Th1/Th2 ratio in all subjects. Results: MiR-451a (P<0.001), Th1 cells (P=0.014), and Th1/Th2 ratio (P<0.001) were increased, while Th2 cells (P<0.001) were declined in sepsis patients compared with HCs. It was of note that miR-451a was positively correlated with Th1 cells (P=0.002) and Th1/Th2 ratio (P=0.001), while it was negatively related to Th2 cells (P=0.005) in sepsis patients. Meanwhile, miR-451a and Th1/Th2 ratio correlated with most of the following indexes: TNF-α, IL-1β, IL-6, C-reactive protein, sequential organ failure assessment (SOFA) score, or Acute Physiology and Chronic Health Evaluation II (APACHE II) score (most P<0.05). Moreover, miR-451a (P<0.001) and Th1/Th2 ratio (P=0.001) were increased in deaths compared to survivors of sepsis, further ROC curve showed both miR-451a and Th1/Th2 ratio possessed a certain value to predict mortality of sepsis patients. Additionally, Th1/Th2 ratio (odds ratio (OR): 2.052, P=0.005) was independently related to 28-day mortality risk from multivariate logistic regression. Conclusion: MiR-451a correlates with Th1/Th2 ratio, and they both relate to inflammation, septic organ injury, and mortality risk in sepsis patients.